Una grande mappa per una piccola isola: il rilevamento delle isole Faroe - Eloise Mitchell (mediaGEO soc. coop., 2021)
The Faroe Islands are a series of islands 300 kilometers North-West of Scotland. The Faroes are part of Denmark and work with the Danish authorities. They have a subpolar climate, and a population of 52,000 people. As the islands are developed and change with new buildings and agriculture, the authorities need up-to-date maps of the islands. The Umhví¸rvisstovan use Pix4Dmatic for large scale mapping on of the land to maintain recent records.